DINAMIKA PENGALAMAN DAN MAKNA PENGGUNAAN AUGMENTED REALITY (AR) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) : STUDI KASUS DI MTS MA’ARIF - Ihda Maulidya Khothrun Nabila; Hamam Burhanuddin (STKIP Subang, 2026)
This study examines in depth the learning experiences of students and teachers when Augmented Reality (AR) technology is integrated into Islamic Religious Education (PAI) classrooms. Using a qualitative approach with a case study design, this research involved two PAI teachers and twelve eighth-grade students at MTs Ma'arif as the main participants. Data were collected through participatory observation, in-depth interviews, and document analysis, which were subsequently analyzed using thematic analysis techniques developed by Braun and Clarke.The findings reveal that the presence of AR has the potential to transform a